PERAN PENDIDIKAN NON FORMAL BERBASIS SOSIAL EKONOMI DALAM ORGANISASI SOSIAL PREMAN SUPER DI MALANG RAYA - Sulistiani, Dwi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
This research with descriptive qualitative method aims to determine how the role of socio-economic-based non-formal education in the organization of Preman Super in the Greater Malang region. The results showed that Preman Super had implemented educational values by dividing two types, namely internal and external education, which meant internal education was that women members were given training, provided with knowledge and were also given the freedom to hone skills according to their potential. it has. Other internal education is a trainer of trainer program or the term is that advanced members can provide training to new members, in accordance with the concept and process of empowerment. External education, which is a number of members who already have experience or have certain skills, will be included in the training held by related agencies that have become partners of Preman Super. In the training the members were given the opportunity to develop talents according to their fields, for example, members who like to cook, then they will be included in cooking training from related agencies and conducted every month. Non-formal education carried out by social organizations Preman SuperÂ  proved effective in increasing women's empowerment in the poor regionÂ Keywords: non-formal education; socio-economic; social organization; preman super; poorÂ